2016
DOI: 10.1080/19440049.2016.1252467
|View full text |Cite
|
Sign up to set email alerts
|

Migration of formaldehyde and melamine from melaware and other amino resin tableware in real life service

Abstract: The migration of formaldehyde and melamine monomers has been measured on 90 samples of plastic tableware in three different situations - new articles, already used articles and artificially aged articles - by using simulant, contact times and temperatures prescribed by Commission Regulation (EU) No. 10/2011. Formaldehyde was determined by ultraviolet spectroscopy analysis of the coloured complex obtained by reaction with chromotropic acid. Melamine was measured by an ultra high performance liquid chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
2
9
1
Order By: Relevance
“…In contrast to migration processes controlled by diffusion and/or partitioning alone, release of melamine and formaldehyde from melamine kitchenware increases in several cases with consecutive migration test cycles due to advanced hydrolysis of the polymer. This has been shown in different studies, e.g., by Mannoni et al [30] and the references therein. Historically, the term "migration" from plastic food contact material was introduced to describe the results of diffusion processes which might be kinetically and/or thermodynamically controlled.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…In contrast to migration processes controlled by diffusion and/or partitioning alone, release of melamine and formaldehyde from melamine kitchenware increases in several cases with consecutive migration test cycles due to advanced hydrolysis of the polymer. This has been shown in different studies, e.g., by Mannoni et al [30] and the references therein. Historically, the term "migration" from plastic food contact material was introduced to describe the results of diffusion processes which might be kinetically and/or thermodynamically controlled.…”
Section: Introductionsupporting
confidence: 58%
“…The F:M ratio ranged between 1.7 and 3.0. This resembles molar ratios typically used for melamine resin production [ 4 , 6 ] and is in the same range as in the so-called import group described in the work of Mannoni et al [ 30 ]. However, in the latter study kitchen also utensils with much higher F:M ratios were found (up to 5.2).…”
Section: Resultsmentioning
confidence: 97%
“…They can be the infant formulae that serve as the only food source of some of the infants, as well as the dietary supplements for some of the pregnant mothers and school children. Nonetheless, melamine indeed exists in many forms in our household and is commonly found in food‐contact materials, most importantly the “melaware”, from which leakage of melamine was detected in many studies . Although the melamine contamination in high dose has ceased, the increased risk of damages to the mothers and fetuses and its developmental adverse outcomes during pregnancy at an intake level lower than the WHO recommendation should be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, melamine indeed exists in many forms in our household and is commonly found in foodcontact materials, most importantly the "melaware", from which leakage of melamine was detected in many studies. [27][28][29][30][31][32] Although the melamine contamination in high dose has ceased, the increased risk of damages to the mothers and fetuses and its developmental adverse outcomes during pregnancy at an intake level lower than the WHO recommendation should be studied.We have previously demonstrated the transfer of low-dose melamine through placenta and mammary gland in a rat model, 33,34 characterized the toxicokinetics of melamine in the pregnant rats, the fetuses and the neonates, 35 and have also proven the reproductive effects in utero. 36 The other published studies of reproductive and developmental effects of melamine in rats have longer administration period, ranging from 8 to 21 days 22-25 but few have focused on the nephrotoxicity…”
mentioning
confidence: 99%
“…On the other hand, several well-known chemicals of concern are used to make plastics and migrate from plastics, for example, BPA, DEHP, and melamine (CAS 108-78-1) [27,28]. Other hazardous chemicals are present as NIAS, like nonylphenol (various CAS, e.g., 84852-15-3), a breakdown product of an antioxidant [29].…”
Section: Changing the Game On Plastics Packaging: Talking Toxicsmentioning
confidence: 99%